Perencanaan Konten Media Sosial Dalam Event Road Tour Legacy Of Java X Sidji Batik Coffee Series - Siti Komsiah; Joachim David Magetanapuang; Cherly Kemala Ulfa; Dewi Maharani Rachmaningsih; Maulidia Eka Sitadewi; William Tristan (Universitas Persada Indonesia YAI, 2022)
The purpose of this research is to design social media content in order to promote the